COMMUNITY EMPOWERMENT THROUGH THE CULTIVATION OF OYSTER MUSHROOMS IN IMPROVING THE ECONOMY - Husni, Mohamad; Setianti, Selda; Indriyanto, Irfan; Paamudiaspuri, Aski Atsriya; Agustina, Melly; Dhaifulah, Adhiya Fauzan (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2024)
Sayar Village has a land area of 1,359,5 hectares with the most significant area being occupied by fields or rice fields of 943 hectares so that the surrounding community works as farmers, but there is still much vacant land that is not utilized optimally by the surrounding community. So, the KKM group 09 Bina Bangsa University carried out an Agricultural Workshop with the theme "Oyster Mushroom Cultivation for the Women Farmers Group (KWT) Hope" held on August 20, 2021. The population and sample of this activi ty were, Student Work Lecture (KKM) Group 09 Bina University The nation was carried out in Cikentang village, Sayar sub-district, Taktakan district, Serang city. 17 students attended KKM Group 09 out of a total of 1,500 students. Accompanied by 1 (One) Field Supervisor (DPL) for each group. The method of this activity starts from the planning, preparation, agricultural workshop activities, evaluation and reporting of activity results. As a follow-up to the KKM workshop, group 09 made a baglog sterilizer. This received a positive response from members of the Harapan Jaya KWT. By holding this activity, it is hoped that it will be able to encourage entrepreneurial interest in mushroom cultivation, both students and the community in Sayar Village and support sustainability with sufficient income to carry out cultivation activities.